Pelatihan Pengolahan Minyak Jelantah dan Sampah Anorganik pada Bank Sampah Melati Bersih Atsiri Permai RW 12, Bojonggede, Kabupaten Bogor - Handayanna, Frisma; Rusiyati, Sri; Purnamasari , Indah (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
Waste is one of the main problems of environmental sustainability, the volume of waste piled up that is not handled properly can pollute the environment, blockages of water channels cause flooding and have various negative impacts on public health, especially inorganic waste from waste that is difficult to decompose naturally. Melati Bersih Atsiri Permai RW 12 Waste Bank with the motto Clean and Smile Movement starting from the 3 R's, namely Reduce, Reuse, Recycle as an institution that drives community empowerment for effective waste management by sorting inorganic waste and collecting used cooking oil as an application of the green economy concept. The problem faced by the Waste Bank is limited knowledge of human resources regarding processing used cooking oil, green economy and inorganic waste. So Nusa Mandiri University lecturers and students held Community Service activities as a 2024 Grant and were funded by the Directorate of Research, Technology and Community Service, Directorate General of Higher Education, Research and Technology, Ministry of Education, Culture, Research and Technology of the Republic of Indonesia . The aim of this activity is to implement used cooking oil processing and create inorganic waste creations according to the green economy concept. The method used is to provide assistance and training in waste bank activities through socialization and training on processing used cooking oil and inorganic waste. The results of the training showed that there was an increase in the participants' knowledge, creativity and innovation in processing used cooking oil into candles and soap, processing inorganic waste into craft creations with high marketability and were motivated to start entrepreneurship.